2000
DOI: 10.1007/bf02360722
|View full text |Cite
|
Sign up to set email alerts
|

Thermotropic gelation in wet spinning of fibres from polymer solutions

Abstract: More than one-third of the chemical fibres manufactured in the world --cellulose, polyacrylonitrile, aramid, polyvinyl chloride, etc. --are now manufactured by wet spinning fi'om polymer solutions. All of these technologies have a common mechanism of fibre formation. Beginning with S. E Papkov's studies [ 1 ], the gelation process in spinning has been considered with respect to the phase state of the polymer solutions. The kinetics of fibre formation (gelation) was investigated experimentally in [2], and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…This phenomenon is called "mechanotropic spinning". 77 Kotomin et al showed that the mechanotropic process has to be taken into account even for ES from polymer solutions. 76 Above all, mechanotropic spinning may be more reasonable for polymer solutions in solvents having low vapor pressures and high boiling points, like DMSO.…”
Section: Polymers Electrospun With Green Solventsmentioning
confidence: 99%
“…This phenomenon is called "mechanotropic spinning". 77 Kotomin et al showed that the mechanotropic process has to be taken into account even for ES from polymer solutions. 76 Above all, mechanotropic spinning may be more reasonable for polymer solutions in solvents having low vapor pressures and high boiling points, like DMSO.…”
Section: Polymers Electrospun With Green Solventsmentioning
confidence: 99%